Teaching children to ignore alternatives is sometimes necessary: indoctrination as a dispensable term - Ariso Salgado, José María (Studies in Philosophy and Education, 2019)
Literature on indoctrination has focused on imparting and revising beliefs, but it has hardly considered the way of teaching and acquiring certaintiesin Wittgenstein's sense. Therefore, the role played by rationality in the acquisition of our linguistic practices has been overestimated. Furthermore, analyses of the relationship between certainty and indoctrination contain major errors. In this paper, the clarification of the aforementioned issues leads me to suggest the avoidance of the term indoctrination' so as to avoid focusing on the suitability of the case to the concept rather than on the analysis of the case itself. This should facilitate that the process of helping children to acquire a world-pictureby teaching them to ignore alternatives to certaintiesis definitely accepted as normal and natural, for many beliefs are expected to end up becoming ungrounded certainties not only in the medium or long term, but also, and above all, in the short term.
Keywords: indoctrination; persuasion; error; Wittgenstein; world-picture; certainty; JCR; Scopus